Use of Dorsal Skin Islands as Firebreak Grafts to the Palm to Reduce the Recurrence Rate of Dupuytren's Contracture. Issue 3 (September 2018) - Kakinoki, Ryosuke; Ohtani, Kazuhiro; Hashimoto, Kazuhiko; Tanaka, Hiroki; Ikeguchi, Ryosuke; Ohta, Souichi; Akagi, Masao
Abstract : Dupuytren's pathologic tissue usually involves the palmar skin and rarely infiltrates into the dorsal skin. In this study, we hypothesized that transplantation of a vascularized cutaneous flap harvested from the dorsum of the hand to the palmar skin, under which the pathologic cord existed might be useful for blocking reformation of the pathologic cords and for decreasing the recurrence rate. After removal of the pathologic tissue under the palmar skin, we harvested 2 types of skin islands nourished by the dorsal digital arterial network including the dorsal perforating arteries arising from the palmar digital arteries. The skin islands were transplanted into skin defects in the palm of the fingers and hand that had been created after correction of flexion contracture of the fingers. We performed this surgical maneuver on 24 fingers in 24 patients who exhibited severe flexion contracture because of Dupuytren disease. During the mean 40-month follow-up, only 1 patient experienced metacarpophalangeal joint flexion contracture ≥20 degrees in the operated finger. The recurrence rate was 4.2%, which was almost similar to that for a dermofasciectomy followed by a large full-thickness skin graft.